ABSTRACTS OF PRESENTED PAPERS FROM THE PARAPSYCHOLOGICAL ASSOCIATION 57TH ANNUAL CONVENTION, CONCORD, CALIFORNIA, USA, AUGUST 14-17, 2014. (Journal of Parapsychology)
The article presents abstracts on parapsychology topics including the testing of retrocausal signaling and temporal loops using electroencephalography (EEG) brain-computer interface, the role of mood on ostensible PK and the alleged telepathic interspecies communication with domestic dogs.